“Ruma Besi” Site as a Media Learning History at Madrasah Aliyah Sairun, Rhun Islands-Banda Naira - Namen, Nursyifa (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The purpose of this study is to show how the historical site "Ruma Besi" in Madrasah Aliyah in the Banda Islands can be utilized as a learning resource for Sejarah Indonesia. This study used a qualitative descriptive method. The results of field observations and relevant reference sources served as the basis for the source consulted for this study. The results show that the historical site "Ruma Besi" (iron house) is a British and Dutch colonial house that originally functioned as the home of the owner of a nutmeg plantation, or Perkenier. Even though only rubble remains, residents said the house was made of iron, starting with supporting pillars, walls, doors, windows, and roofs. Residents of Rhun Island today know it better as a "house of entertainment" because the site reminds them more of the attractions of Javanese dancers accompanied by Javanese music, which always decorated the afternoon breaks of nutmeg plantation workers at that time. The process of utilizing the historical site "Ruma Besi" as a learning resource for Indonesian history for Madrasah students is carried out by imagining historical facts about Indonesia in the past through a simple research step or discovery inquiry, which allows students to be directly involved as actors in activities. Historical discovery and study. This process is very beneficial for a complete understanding of historical material because of its closeness to the locus and its direct involvement in learning and introducing historical information.   Keywords: Ruma Besi, Media Learning History, Rhun Island, Banda Naira